Educational Management in Quranic Education Centers: A Study on Education Personnel, Facilities, and Public Relations - Iswandi, Iswandi; Fitriyah, Fitriyah; Lestari, Puja (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study investigates the management practices in Quranic education centers (TPQs), focusing on three key domains: education personnel management, facilities and infrastructure, and public relations. Using a qualitative approach, data were collected through interviews, observations, and document analysis in selected TPQs. The findings reveal significant challenges in recruiting and retaining qualified educators, disparities in facilities due to varying levels of community support, and a lack of structured public relations strategies. However, centers with strong community engagement demonstrated better outcomes in all three domains. The study highlights the interconnectedness of these management areas, where improvements in one domain positively impact others. An integrated management framework is proposed to address these challenges, emphasizing the alignment of personnel management, infrastructure development, and public relations. This framework offers practical implications for policymakers and practitioners to enhance the quality and sustainability of TPQs. Future research is recommended to explore the applicability of this framework in diverse cultural and regional contexts.